PENERAPAN MODEL ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA MATERI KERAGAMAN DI SEKITARKU PADA SISWA KELAS IV SD NEGERI 066047 HELVETIA - Patri Janson Silaban; Eglauri Agata Manihuruk; Fitri Rahmadani Hadi; Geofani Asima Sitinjak (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve learning outcomes in Pancasila Education on the topic of "Diversity in My Surroundings" through the implementation of the Role Playing learning model among fourth-grade students of SD Negeri 066047 Helvetia. This classroom action research was conducted in two cycles, each consisting of planning, action, observation, and reflection phases. The research subjects were 18 fourth-grade students. The findings indicate that the application of the Role Playing model effectively enhanced student participation and learning outcomes. In the initial stage (pre-cycle), only 28% of students achieved the minimum competency standard, with an average score of 62. After implementing the Role Playing model, learning outcomes improved to 67% in the first cycle and reached 89% in the second cycle, with an average score of 77. Additionally, the Role Playing model created an engaging learning environment and encouraged active student participation. Thus, the implementation of the Role Playing model proved to be effective in improving learning outcomes in Pancasila Education, especially for topics requiring understanding of social diversity. This study recommends using the Role Playing model in teaching to foster interactive classrooms and enhance students' motivation to learn.